Divine traditions and the governance of the city-state of Medina - Ali, Ishraq (HTS teologiese studies, 2024)
Divine revelations in Islam are not restricted to the spiritual well-being of its followers but aim to guide them towards the realisation of a socio-political organisation, a polity, wherein they can achieve spiritual as well as socio-political excellence. Because of the immense significance of socio-political organisation in Islam, the governance of socio-political organisation is one of the key topics in Islam. The principles of the governance of socio-political organisation in Islam are based on certain divine traditions. This article focusses on five major Islamic divine traditions outlined in Islamic revelatory culture: firstly, the divine tradition of guidance and misguidance; secondly, the divine tradition of Ni’mat [Blessings] and their reversal; thirdly, the divine tradition of the triumph of Haqq’ [Truth] over Báṭil [Falsehood]; fourthly, the divine tradition of the destruction of the oppressors and fifthly, the divine tradition of trial. This article attempts to show that these five Islamic divine traditions form the foundation for the structure and function of the governance system of the first Muslim polity, the city-state of Medina.Contribution: This article highlights the role of Islamic divine traditions in the structure and function of the governance system of the first Muslim polity, the city-state of Medina.